PENGARUH MANAJEMEN LABA RIIL DAN PENGUNGKAPAN TATA KELOLA TERHADAP TAX AVOIDANCE - Evan Christian; Estralita Trisnawati (Jurnal Paradigma Akuntansi, 2023)
The purpose of this study is to obtain empirical evidence about the effect of Real Earnings Management and Corporate Governance Disclosure on Tax Avoidance on the manufacturing firms listed on the Indonesia Stock Exchange during 2017 – 2019. Sample was selected using purposive sampling method and the valid data was 128 samples companies. Data processing techniques using multiple regression analysis. This study used Statistical Package for the Social Sciences (SPSS) ver. 25 software and SmartPLS ver. 3.3.2 software. The result show that real earnings management have a positif influence on tax avoidance and corporate governance disclosure does not significantly influence tax avoidance. The implication of this study is the need to increase monitoring of real earnings management and corporate governance disclosure to avoid tax avoidance.